Assessment of Ecological Predictors of Moral Decadence in Oyo State, Nigeria (2022)
This study was carried out to determine the factors responsible for moral decadence in the characteristics of the adolescents and young children in Nigeria with the hope that such findings will pave the way to remedy that will safeguard total collapse of this country. The study adopted a descriptive research design of survey type. The population of the interest cut across the age categories of adults from age 30 and above. Stratified random sampling was used for the study. The population involved were male and female and of different ethnic groups Yoruba, Hausa and Igbo. A self-administered method of data collection was used with a reliable and valid instrument. The instrument was divided into six categories. The first category measured the demographic information of the respondents, while sections B to F measured the government, society, school, religious organisations, the parents and the children themselves a contribution to the adolescents and youths moral decadence in the state. The reliability coefficient of the instrument is 0.87. The instrument response format is likert form, ranging from strongly agree to strongly disagree. The results showed that the government, society, parents, school and religious organisations have lost the expected roles on morality. Parenting style, unwillingness to take to correction by the children, get-rich-quick syndrome, parents looking for money at the detriment of taking care of the children, possession of the sophisticated phone, exposure to bad films; the use of hard drugs, broken home; age at marriage, not having good role model, unemployment and so on, and many others are the reasons why the society has turned upside down. The researcher concluded that the problems with children are caused by the government, schools and religious organisations, society, parents and the children themselves. Recommendations were made that urgent attention should be taken to forestall the total collapse of the value system in the country, that schools and religious organisations should do the needful.